Kemampuan Menyimak Bahasa Jerman dengan Menggunakan Aplikasi Seedlang - Elma Wanda Septari; Misnah Mannahali; Syamsu Rijal (Academic : Journal of Social and Educational Studies, 2024)
Abstract. This study aims to determine the planning, implementation and results of improving German listening skills through the Seedlang application. This research is a classroom action research consisting of two cycles with each cycle consisting of planning, implementation, observation and reflection stages. This research data consists of two types of data, namely qualitative data which is a description of the results of implementation and observation during learning and quantitative data in the form of student listening skills test results. The average value of improving the listening skills of XI MIPA 3 class students in cycle I was 66.42% (good) then in cycle II it increased to 87.42% (very good). The results showed that the use of the Seedlang application can improve students' German listening skills during learningKeywords: Listening, Media, Seedlang, German